2010
DOI: 10.1097/hjh.0b013e328332bc87
|View full text |Cite
|
Sign up to set email alerts
|

Human dopamine beta-hydroxylase (DBH) regulatory polymorphism that influences enzymatic activity, autonomic function, and blood pressure

Abstract: Rationale Dopamine beta-hydroxylase (DBH) plays an essential role in catecholamine synthesis by converting dopamine into norepinephrine. Here we systematically investigated DBH polymorphisms associated with enzymatic activity as well as autonomic and BP/disease phenotypes in vivo. Methods and Results 70 genetic variants were discovered at the locus; across ethnicities, much of the promoter was spanned by a 5’ haplotype block, with a larger block spanning the promoter in whites than blacks. DBH secretion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 61 publications
3
58
1
Order By: Relevance
“…19 However, it remains unknown how rs1611115- T reduces circulating DBH and norepinephrine levels. Reporter gene assays in rat PC12 chromaffin cells have yielded opposing results with rs1611115, 1719 and whether this effect applies in vivo in human cell types remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, it remains unknown how rs1611115- T reduces circulating DBH and norepinephrine levels. Reporter gene assays in rat PC12 chromaffin cells have yielded opposing results with rs1611115, 1719 and whether this effect applies in vivo in human cell types remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP), located 1,021 bp 5 0 to the transcriptional start site of DBH (À1021C/T; rs1611115) has been reported to account for 30-50% of the variance in serum DbH, depending on the geographic origin or ethnicity of samples [Zabetian et al, 2001;Tang et al, 2005Tang et al, , 2006Tang et al, , 2007Bhaduri and Mukhopadhyay, 2008]. Individuals with CC genotype had the highest levels of DbH plasma activity and TT genotype was the lowest with CT being intermediate, suggesting a co-dominant inheritance or a gene-dose effect [Cubells and Zabetian, 2004;Tang et al, 2006], respectively Importantly, a recent study [Chen et al, 2010] reported in vitro and in cellar evidence that rs1611115 (reported as À970C>T in their study) alters the transcription of DBH, strongly supporting this SNP is functional.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 99%
“…We selected the À1021C/T polymorphism because it has thus far the strongest evidence to be a functional one in DbH [Chen et al, 2010] and at least one study suggests that CC genotype of this SNP was associated with a diminished performance of EF (as reflected by a composite measure, CPT, and Wisconsin card sorting test) [Kieling et al, 2008]. In addition, previous studies from our group have shown possible association between this polymorphism and ADHD phenotypes in Chinese population, but the preferentially transmitted alleles differ between subtypes [Zhang et al, 2004[Zhang et al, , 2005.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 99%
“…DBH is also released from central noradrenergic neurons. Variation in DBH activity appears highly heritable, with environmental factors having relatively little effect [15]. Studies have previously shown that DBH inhibition attenuates development of hypertension in the spontaneously hypertensive rat [16].…”
Section: The Neurogenic Hypothesismentioning
confidence: 99%
“…Chen and colleagues explored the role of DBH promoter variant C-970T, finding that this particular variant influenced heritable traits in twin pairs that may mark individuals at risk of developing hypertension in later life. Possession of the minor (T) allele appears to predict lower DBH activity, lower systolic blood pressure in response to stress, and decreased catecholamine excretion across a variety of ethnic groups [15]. The same researchers went on to identify C-2073T, a second functional variant in the DBH promoter.…”
Section: The Neurogenic Hypothesismentioning
confidence: 99%